Impact of vitamin D on the course of COVID-19 during pregnancy: A case control study. Issue 213 (October 2021) - Sinaci, Selcan; Ocal, Doga Fatma; Yucel Yetiskin, Didem Fatma; Uyan Hendem, Derya; Buyuk, Gul Nihal; Goncu Ayhan, Sule; Tanacan, Atakan; Ozgu-Erdinc, A. Seval; Moraloglu Tekin, Ozlem; Sahin, Dilek
Graphical abstract: Highlights: Pregnant COVID-19 patients tend to have lower vitamin D levels than healthy ones. Healthy pregnant women are likely to have vitamin D deficiency and insufficiency. Vitamin D deficiency may affect the course of COVID-19 in pregnant patients. Vitamin D deficiency can be thought of as a risk factor for severe COVID-19. Abstract: Objective: We aimed to evaluate the vitamin D status of pregnant women with COVID-19, and the association between vitamin D level and severity of COVID-19. Methods: In this case control study, 159 women with a single pregnancy and tested positive for SARS-CoV-2, and randomly selected 332 healthy pregnant women with similar gestational ages were included. COVID-19 patients were classified as mild, moderate, and severe. Vitamin D deficiency was defined as 25-hydroxycholecalciferol <20 ng/mL (50 nmol/L), and 25-OH D vitamin <10 ng/mL was defined as severe vitamin D deficiency, also 25-OH D vitamin level between 20−29 ng/mL (525−725 nmol/L) was defined as vitamin D insufficiency. Results: Vitamin D levels of the pregnant women in the COVID-19 group (12.46) were lower than the control group (18.76). 25-OH D vitamin levels of those in the mild COVID-19 category (13.69) were significantly higher than those in the moderate/severe category (9.06). In terms of taking vitamin D supplementation, there was no statistically significant difference between the groups. However, it was observed that all of those who had severe COVID-19 were the patients who did not take vitamin D supplementation. Conclusion: The vitamin D levels are low in pregnant women with COVID-19. Also, there is a significant difference regarding to vitamin D level and COVID-19 severity in pregnant women. Maintenance of adequate vitamin D level can be useful as an approach for the prevention of an aggressive course of the inflammation induced by this novel coronavirus in pregnant women.